Identification of Novel Genes Involved in the Pathogenesis of an ACTH-Secreting Pituitary Carcinoma: A Case Report and Literature Review - Guo, Fuyou; Wang, Guoqing; Wang, Fang; Xu, DingKang; Liu, Xianzhi (Frontiers in Oncology, 2018)
Abstract Pituitary carcinomas (PCs) is considerable uncommon entities with a poor prognosis that represents only 0.1-0.2% of all pituitary tumors. There are fewer than 150 reported cases up to now. In addition, the molecular pathogenesis leading to malignant pituitary transformation remain unclear due to the rarity of PCs. Here we present an uncommon case of ACTH-secreting PCs and explore the gene mutation following pituitary adenoma transformation. Our detailed clinical, histopathological and molecular detection data suggest that novel genes of ATRX and PTEN were implicated in the pathogenesis of PCs by searching Pubmed and the Web of Science databases as well as Cosmic databank. To the best of our knowledge, this is the first documented rare PCs patient with novel gene mutations that included ATRX and PTEN in addition to TP53. Present finding may therefore provide significant information for targeted therapy of PCs.